Fairness views and cooperation under varying levels of economic inequality - Hariskos Wasilios; Neitzel Jakob; Sääksvuori Lauri (Public Library of Science (PLoS), 2025)
This paper investigates the impact of economic inequality on people's perceptions of fairness and willingness to cooperate. Using experimental and survey data, we distinguish people's injunctive perceptions of fairness from experimentally observed behavioral patterns. We find that impartial observers hold shared perceptions of fair contribution rules. Individuals with their own money at stake hold conflicting views over fair contribution rules. We find that contribution patterns are more scattered under strong inequality than under weak inequality. Overall, we observe that voluntary contributions are lower under strong inequality than under weak inequality. Our results contribute to the debate about the behavioral consequences of income and wealth inequalities in modern societies.